Ectopic osteogenesis by type I collagen loaded with a novel synthesized PTH‐related peptide‐1 in vivo. Issue 1 (9th October 2019) - Wang, Yi; Wang, Jianping; Zheng, Jin; Yu, Mingxia; Cai, Lin; Zhang, Shuwei; Li, Jingfeng
Abstract: This study aims to investigate the ability of parathyroid hormone (PTH)‐related peptide‐1/type I collagen (PTHrP‐1/Col‐I) scaffold material to induce ectopic osteogenesis in the quadriceps muscle pocket of Sprague–Dawley (SD) rats. A novel peptide PTHrP‐1 was derived from PTH and used at different concentrations (0, 0.1, 0.3, and 0.5 mg/ml) to induce ectopic osteogenesis. Radiographic examinations (X‐ray, CT, and 3D reconstruction), pathological observations (H&E, Masson, Von Kossa, ALP and TRAP staining), immunohistochemical staining (Col‐I, OCN and Runx‐2 in tissues), western blotting was used to determine the qualitative and quantitative analysis of related markers proteins. Results confirmed that the appropriate concentration of PTHrP‐1 can effectively enhance the osteogenic activity, thereby improving the positive results and protein expression of osteogenic markers (COL‐I, OCN, and Runx‐2) in the quadriceps muscle pocket of SD rats. Through qualitative and quantitative analysis, high concentration of PTHrP‐1 promotes osteogenic activity and active bone resorption. This study confirmed that PTHrP‐1 is a novel small molecule bioactive peptide, and the rat tail collagen scaffold is a good carrier of PTHrP‐1 with excellent biocompatibility. The PTHrP‐1/Col‐I composite scaffold material is an effective substitute for bone tissue engineering and can effectively induce and promote bone formation in the quadriceps muscle pocket of rats. In addition, the promoting ability for osteogenic differentiation of 0.3 mg/ml PTHrP‐1/Col‐I composite scaffold material group was significantly better than that of 0, 0.1 and 0.5 mg/ml PTHrP‐1/Col‐I composite scaffold material groups. Hence, the optimal concentration of PTHrP‐1 to promote ectopic osteogenesis is 0.3 mg/ml.